Caveolin-mediated endocytosis of the Chlamydia M278 outer membrane peptide encapsulated in poly(lactic acid)-Poly(ethylene glycol) nanoparticles by mouse primary dendritic cells enhances specific immune effectors mediated by MHC class II and CD4+ T cells. (March 2018) - Dixit, Saurabh; Sahu, Rajnish; Verma, Richa; Duncan, Skyla; Giambartolomei, Guillermo H.; Singh, Shree R.; Dennis, Vida A.
Abstract: We previously developed a Chlamydia trachomatis nanovaccine (PPM) by encapsulating a chlamydial M278 peptide within poly(lactic acid)-poly(ethylene glycol) biodegradable nanoparticles that immunopotentiated Chlamydia -specific immune effector responses in mice. Herein, we investigated the mechanistic interactions of PPM with mouse bone marrow-derived dendritic cells (DCs) for its uptake, trafficking, and T cell activation. Our results reveal that PPM triggered enhanced expression of effector cytokines and chemokines, surface activation markers (Cd1d2, Fcgr1), pathogen-sensing receptors (TLR2, Nod1), co-stimulatory (CD40, CD80, CD86) and MHC class I and II molecules. Co-culturing of PPM-primed DCs with T cells from C. muridarum vaccinated mice yielded an increase in Chlamydia -specific immune effector responses including CD3 + lymphoproliferation, CD3 + CD4 + IFN-γ-secreting cells along with CD3 + CD4 + memory (CD44 high and CD62L high ) and effector (CD44 high and CD62L low ) phenotypes. Intracellular trafficking analyses revealed an intense expression and colocalization of PPM predominantly in endosomes. PPM also upregulated the transcriptional and protein expression of the endocytic mediator, caveolin-1 in DCs. More importantly, the specific inhibition of caveolin-1 led to decreased expression of PPM-induced cytokines and co-stimulatory molecules. Our investigation shows that PPM provided enhancement of uptake, probably by exploiting the caveolin-mediated endocytosis pathway, endosomal processing, and MHC II presentation to immunopotentiate Chlamydia -specific immune effector responses mediated by CD4 + T cells.